2019
DOI: 10.3390/su11102986
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of R&D and the Control–Ownership Wedge on Firm Value: Evidence from Korean Chaebol Firms

Abstract: Cases have been reported in which research and development (R&D) investment, the core activity for a firm’s sustainable growth, deteriorate rather than increase firm value. This study illuminates the cause of such cases in terms of the control–ownership wedge. How expensed and capitalized R&D affect firm value are examined separately for cases in which the wedge is high and low. In an analysis of Korean chaebol firms, when the wedge is high, significant negative relationships appear between expensed R&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The author of [49] tested the relationship between ownership concentration measured by individually controlling shareholders' percentages and institutionally controlling shareholders and firm value; he found that both measures push down the firm value in Switzerland. Likewise, the expropriation impact of ownership concentration in the Korean market deepens the negative R&D-firm value relationship because of controlling shareholders hindering R&D investment decisions [50]. Meanwhile, a third line of research revealed no clear link between ownership concentration and firm performance; the authors of [51] reported that a high level of control by family or state shareholders in Arab Gulf listed companies did not show a significant impact of ownership on the market to book ratio.…”
Section: The Role Of Ownershipmentioning
confidence: 99%
“…The author of [49] tested the relationship between ownership concentration measured by individually controlling shareholders' percentages and institutionally controlling shareholders and firm value; he found that both measures push down the firm value in Switzerland. Likewise, the expropriation impact of ownership concentration in the Korean market deepens the negative R&D-firm value relationship because of controlling shareholders hindering R&D investment decisions [50]. Meanwhile, a third line of research revealed no clear link between ownership concentration and firm performance; the authors of [51] reported that a high level of control by family or state shareholders in Arab Gulf listed companies did not show a significant impact of ownership on the market to book ratio.…”
Section: The Role Of Ownershipmentioning
confidence: 99%
“…In the hotel industry, profitability measures including net profit, gross profit, and operating profit margins are frequently employed to evaluate financial stability and profitability. Gross profit margin reflects the hotel's ability to control direct expenses, operating profit margin measures profitability after accounting for operating expenses, and net profit margin assesses overall profitability considering all expenses (Kim & Kim, 2019). These financial performance measures, including net profit, gross profit, and operating profit margins, are commonly utilized to measure the monetary health and effectiveness of hotels in generating profits (Gibson & Dennett, 2018).…”
Section: Introductionmentioning
confidence: 99%